2007
DOI: 10.1007/s12098-007-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of living in lead mining area on growth

Abstract: Regarding the results of this study, environmental exposure due to living in lead mining area can lead to increased BLL in children. In addition, our results suggest there is no significant effect of BLL on growth parameters in children in lead mining area. Since some clinical and sub clinical problems are strongly probable when BLL is increased, special attention of the relevant organizations and more research about the problem and its outcome, is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…35 μg/dL). Also there was no significant difference in growth parameters, including weight and height, in the children of two groups [131], suggesting that the BLL was not correlated with growth parameters of children in lead mining area. In another survey, the average intelligence quotient (IQ) in 64 children living in high lead area of Zanjan province (Center of Iran) was 86.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…35 μg/dL). Also there was no significant difference in growth parameters, including weight and height, in the children of two groups [131], suggesting that the BLL was not correlated with growth parameters of children in lead mining area. In another survey, the average intelligence quotient (IQ) in 64 children living in high lead area of Zanjan province (Center of Iran) was 86.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Also, linear height growth in postnatal first 48 months of lead exposure was not statistically significant in comparison to the prenatal period (18). In the study of Mahram et al, lead exposure did not have a negative effect on height growth (27). While in the study of Sanna et al conducted in Italy, significant effect of lead exposure on height growth in 11-to 14 -year -old children in comparison with the control group was mentioned (25).…”
Section: Discussionmentioning
confidence: 83%
“…Six studies found that exposure to lead could have a negative influence on children and adolescents' height (21)(22)(23)(24)(25)(26). A study reported an association between higher blood lead levels and shorter average height, yet this result was not statistically significant in comparison to controls (27). Overall, eight to ten articles had referred to the impact of lead on short stature and two other papers did not confirm this relationship.…”
Section: Air Pollutantsmentioning
confidence: 98%
“…A prevalência em amostra populacional norte americana de níveis acima de 10 µg/dL na idade de um ano foi em torno de 17% e, retestados aos 24 meses a taxa foi de 29%. 14 Existem evidências de que, em crianças, o chumbo em excesso produz efeitos adversos em rins 19 e sistema hematopoiético, 20 interfere no peso ao nascimento, 21 perímetro craniano 22 e há controvérsias quanto ao crescimento; 23 reduz a acuidade auditiva e equilíbrio, além de séria interferência nas funções cognitivas. 24,25,26 Needleman et al (1972) 24 foi um dos pioneiros na luta para o reconhecimento dos efeitos danosos desse metal e apresentaram os primeiros estudos em crianças americanas.…”
unclassified